Inpatient Biophysical Profiles and the Effect on Clinical Decision Making - Diana A. Racusin; Suneet P. Chauhan; Baha Sibai; Han-Yang Chen; Nesochi Adimorah; Mica Piro; Kristen Heye; Charlotte Sharp; MSN WHNP-BC; Sean Blackwell; Jerrie Refuerzo (Thieme Medical Publishers, Inc., 2020)
Objective Our primary objective was to determine whether biophysical profiles (BPP) performed on the antepartum unit result in changes in clinical decision making. Study Design A retrospective cohort chart review was performed among women who had a BPP during hospital admission. BPP status was categorized as normal (8/8 points) and abnormal (6/8 or less points). The primary outcome, clinical decision making, was the need for prolonged external fetal monitoring (defined as > 2 hours) or decision to proceed with delivery. Secondary outcomes included mode of delivery, indicated preterm delivery, birth weight, 5-minute Apgar's score <7, and neonatal intensive care unit (NICU) admission. Results Among our cohort (n = 186), 85.5% (n = 159) had a normal BPP. Delivery management was altered in one case (0.54%) by the BPP findings, and there were no BPPs that resulted in need for prolonged monitoring. Compared with women with normal BPP, women with abnormal BPPs were more likely to deliver at <37 weeks, to be admitted to the NICU, or have a 5-minute Apgar's score <7. Conclusion In-hospital BPPs alter clinical decision making in less than 1% of cases.